2020
DOI: 10.1108/jfep-02-2020-0021
|View full text |Cite
|
Sign up to set email alerts
|

Financial inclusion and business cycles

Abstract: Purpose This study aims to investigate the relationship between financial inclusion and the business cycle. Design/methodology/approach Regression methodology is used to analyze the association between financial inclusion and the business cycle. Findings Using regression estimation, the findings reveal that the level of savings and the number of active formal account ownership are pro-cyclical with fluctuations in the business cycle. Also, savings by adults particularly for women and poor people declines d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Notwithstanding, this study has made an important contribution to the limited body of literature on the relevance of financial inclusion in reducing the size of shadow economy. Future studies may look at the threshold value of financial inclusion to avoid possibility of extreme financial inclusion as suggested by Ozili (2020a, 2020b). It would be of interest if future studies can increase the number of sample size and examine whether similar results hold for other developing countries in Latin America and Asia countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding, this study has made an important contribution to the limited body of literature on the relevance of financial inclusion in reducing the size of shadow economy. Future studies may look at the threshold value of financial inclusion to avoid possibility of extreme financial inclusion as suggested by Ozili (2020a, 2020b). It would be of interest if future studies can increase the number of sample size and examine whether similar results hold for other developing countries in Latin America and Asia countries.…”
Section: Discussionmentioning
confidence: 99%
“…This means that a country with good regulatory financial system may possibly have little or no shadow economy (Blackburn et al , 2012; Bose et al , 2012). However, for effective financial inclusion system, policy time lag is crucial as revealed by Ozili (2020a, 2020b). The author explains that policymakers wishing to achieve the goals of financial inclusion must consider the policy time lag along with the business cycle.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings of the present study have shown that high levels of EPU had some depressive effects on financial inclusion. Secondly, this study contributes to the financial inclusion literature (see, Mindra et al, 2017;Ozili, 2020a;Zins & Weill, 2016;Ozili, 2020b). The study showed that EPU is a determinant of the level of financial inclusion.…”
Section: Introductionmentioning
confidence: 72%
“…They found that the per capita real GDP had a positive influence on the level of financial inclusion in developing countries. Ozili (2020b) investigated financial inclusion through the business cycle. The study used the GDP growth rate to measure the state of the business cycle.…”
Section: Determinants and Consequences Of Financial Inclusionmentioning
confidence: 99%
See 1 more Smart Citation